PROBLEMS OF OUTCOMES CHOICE FOR THE ASSESSMENT OF REHABILITATION PROGRAMS EFFICIENCY IN PATIENTS AFTER STROKE AND CRANIOCEREBRAL INJURY - V. S. Dombrovskiy; V. V. Omelyanovskiy (Фармакоэкономика)
this article considers the appropriateness of surrogate points and endpoints utilization as evaluation criteria for rehabilitation programs efficiency in patients after stroke, craniocerebral injury or other CNS diseases (e.g. tumors, neuroinfections etc.) in Russian Federation. The purpose of this study is to evaluate surrogate and final outcomes of neurorehabilitation program in patients after stroke and craniocerebral injury. Materials and methods. The study was carried out using data provided by the Center of speech pathology and neurorehabilitation. A notion of Social status recovery was selected as an economically significant surrogate outcome which was evaluated by physicians at the end of the rehabilitation course. A notion of Disability conferred by the Federal State Institutions of Disability Evaluation was selected as an economically significant final outcome. Surrogate and final outcomes comparison was performed based on the regulatory materials. Results. Surrogate outcomes evaluation revealed that at the end of rehabilitation course most patients (86.64%) reached the level of social and living needs, i.e. they have an ability to live and to take care for themselves without assistance. Final outcomes evaluation revealed that proportion of patient without disability decreased by 4-fold between the first and second visits and that total changes in disability degree by the time of the last visit were significantly smaller in comparison with the second patient's visit to the Center. Comparison of surrogate and final outcomes revealed significant discrepancy between the patient's status characteristics. Thus, in the disability group I only 7.66% of patients were actually unable to perform activities of daily living without assistance, while 90.46% of patients were able to live without assistance, that corresponds to the disability group II. Conclusion. Established degree of disability often does not correspond to the actual patient's state. The analysis based on the disability group changes is not sensitive enough for the evaluation of rehabilitation programs efficacy. Therefore, the use of indirect signs of economically significant recovery seems to be more appropriate for the efficacy evaluation of such technology.